2017
DOI: 10.3126/jbs.v3i1.16846
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of carbapenem resistant bacterial strains isolated from different clinical samples: study from a tertiary care hospital in Kathmandu, Nepal

Abstract: Background Carbapenems are considered as drugs of choice for the treatment of the infections caused by drug resistant bacteria. However, in the recent years the prevalence of carbapenem resistant gram negative bacteria has increased significantly. The main objective of this study was to determine the prevalence of carbapenemase producing gram negative bacteria among all the clinical isolates.Material and methods A total of 3246 non-repeated, different clinical specimens from patients attending Kathmandu Model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 25 publications
3
21
5
Order By: Relevance
“…(54.54%) whereas lowest from P. vulgaris (7.69%). These results were less than outcomes of previous studies (Karn et al 2016) A (Dalela 2012) study showed that imipenem is the most active drug for the treatment of infections which are caused by ESBL producers, followed by Amikacin which is similar to our fi nding. 7.48% isolates were found to be MBL producers which is higher than Mishra et al 2012 (1.3%) and lesser than Haider et al 2014 (17.93%) highest MBL producer being Pseudomonas aeruginosa (Mishra et al 2012) and ( Haider et al 2014).…”
Section: Methodscontrasting
confidence: 86%
“…(54.54%) whereas lowest from P. vulgaris (7.69%). These results were less than outcomes of previous studies (Karn et al 2016) A (Dalela 2012) study showed that imipenem is the most active drug for the treatment of infections which are caused by ESBL producers, followed by Amikacin which is similar to our fi nding. 7.48% isolates were found to be MBL producers which is higher than Mishra et al 2012 (1.3%) and lesser than Haider et al 2014 (17.93%) highest MBL producer being Pseudomonas aeruginosa (Mishra et al 2012) and ( Haider et al 2014).…”
Section: Methodscontrasting
confidence: 86%
“…Studies from other hospitals have reported MBL as the most common carbapenamase among the non-fermentative Gram negative bacteria. 27,28 The prevalence of carbapenamase has been reported from 4% to 74%. [29][30][31][32] Recent studies from other hospitals of Nepal reported the prevalence of carbapenam resistance from 4.5%-86.4%.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Recent studies from other hospitals of Nepal reported the prevalence of carbapenam resistance from 4.5%-86.4%. 21,27 This reflects that the prevalence varies from hospital to hospital within a country. Colistin and tigecycline are effective against carbapenamase producing strains of Acinetobacter species with low level of resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In Nepal, previous studies have reported the prevalence of carbapenem resistance in Gram-negative bacteria. [15][16][17][18][19] Studies have reported varying prevalences of carbapenem resistance in bacteria in different settings, including 7.4% in Model Hospital, Kathmandu, 15 12.6% in the Human Organ Transplant Center, Bhaktapur, 16 7.6% in Tribhuvan University Teaching Hospital, Maharajgunj, Kathmandu, 18 and 27% in Kathmandu University Teaching Hospital, Sinamangal, Kathmandu. 17 Another similar study, conducted in Bharatpur, Hospital, Chitwan, reported a 40% prevalence of carbapenem-producing Enterobacterales; 41.3% E. coli and 57.1% K. pneumoniae isolates.…”
Section: Introductionmentioning
confidence: 99%